A deflategate analysis for the NBA - Beuoy. M. (Inpredictable, 2017)
The NFL's Deflategate scandal was long on rumor and insinuation, but short on hard data (i.e. the makings of a good scandal). It boiled down to just 30 data points: two separate pressure gauge readings of 11 Patriots footballs and 4 Colts footballs, taken at halftime of the 2015 AFC Conference championship. You can breathe a sigh of relief, because I'm certainly not going to rehash that analysis here.